2008
DOI: 10.1094/phyto-98-12-1312
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Recombination in the Botrytis cinerea Populations in Hungarian Vineyards

Abstract: Botrytis cinerea (anamorph of Botryotinia fuckeliana) causes gray mold on a high number of crop plants including grapes. In this study, we investigated the genetic properties of a grape pathogenic population of B. cinerea in the area of Eger, Hungary. A total of 109 isolates from 12 areas were sampled. Based on the sequence of the beta-tubulin (tub1) locus, they all belong to group II, a phylogenetic species within B. cinerea. Seventy-four isolates were classified as transposa, with both the Flipper and Boty t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
3
33
0
3
Order By: Relevance
“…The other isolate types found in our samples were: boty isolates (21.2%), flipper isolates (9.1%), and vacuma isolates (6.1%). This result was in agreement with previous studies that had demonstrated the significant predominance of transposa type [19] [45]- [47]. Otherwise, the vacuma isolates had been previously reported as a predominant type in other host plants [37].…”
Section: Discussionsupporting
confidence: 93%
“…The other isolate types found in our samples were: boty isolates (21.2%), flipper isolates (9.1%), and vacuma isolates (6.1%). This result was in agreement with previous studies that had demonstrated the significant predominance of transposa type [19] [45]- [47]. Otherwise, the vacuma isolates had been previously reported as a predominant type in other host plants [37].…”
Section: Discussionsupporting
confidence: 93%
“…Frequencies varying from 10 to 16% have been reported in Hungarian vineyards and California, respectively (Váczy et al. ; Ma and Michailides ). Because the boty genotype was not described as part of the Group II (Fournier et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Váczy et al. ), clone mates were identified by calculating the probability ( P GEN ) of each multilocus genotype (MLG) arising through sexual instead of clonal reproduction using the software genclone V2.0 (Arnaud‐Haond and Belkhir ). Isolates which shared MLGs with P GEN < 0.05 were considered as having undergone clonal reproduction.…”
Section: Methodsmentioning
confidence: 99%